Evaluation of External Apical Root Resorption in Cases with Extraction and Non-Extraction Fixed Orthodontic Treatment - Peker, Ramazan Berkay; Meriç, Pamir (Diagnostics (Basel), 2024)
Objective: The objective of this study was to evaluate external apical root resorption (EARR) in cases with extraction and non-extraction fixed orthodontic treatment. Methods: Ninety subjects were included in this study. The patients were divided into two groups: 43 with extraction treatment and 47 with non-extraction orthodontic treatment. EARR was measured using the crown-to-root ratio of the maxillary and mandibular incisors and canines on panoramic radiographs taken at the beginning (T0) and end of the treatment (T1). The Bonferroni corrected Z test was used for multiple comparisons. Results: There were 24 (55.8%) individuals in the extraction group and 12 (25.5%) in the non-extraction group, with a minimum of one tooth with severe resorption. There was no resorption in 0% of individuals in the extraction group and five (10.6%) individuals in the non-extraction group. There was a statistically significant correlation between the groups and the degree of resorption (p = 0.008). When the maxillary and mandibular teeth in the extraction group were compared, a significant difference was found in all degrees of resorption except for mild resorption. Conclusions: There was a significant difference in EARR between the extraction and non-extraction treatment groups, with maxillary incisors showing more resorption in the extraction treatment.